2014
DOI: 10.1124/jpet.114.219832
|View full text |Cite
|
Sign up to set email alerts
|

Demethyleneberberine, a Natural Mitochondria-Targeted Antioxidant, Inhibits Mitochondrial Dysfunction, Oxidative Stress, and Steatosis in Alcoholic Liver Disease Mouse Model

Abstract: Excessive alcohol consumption induces oxidative stress and lipid accumulation in the liver. Mitochondria have long been recognized as the key target for alcoholic liver disease (ALD). Recently, the artificial mitochondria-targeted antioxidant MitoQ has been used to treat ALD effectively in mice. Here, we introduce the natural mitochondria-targeted antioxidant demethyleneberberine (DMB), which has been found in Chinese herb Cortex Phellodendri chinensis. The protective effect of DMB on ALD was evaluated with He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…This induction correlates with increased oxidative stress in rats; however, the increased oxidative stress was attenuated by the addition of medium-chain triglycerides 140 . The mitochondrial-targeted antioxidant demethyleneberberine (DMB) from the Chinese herb Cortex Phellodendri chinensis also has a protective effect in acutely and chronically ethanol-treated mice 141 . DMB suppressed the 2–3-fold ethanol induction of mtCYP2E1 in liver mitochondria for both 52 kDa and 40 kDa enzyme forms (as shown by Western blot of purified mitochondrial fractions), as well as attenuated the 1.5-fold ethanol induction of overall total liver CYP2E1 (mt+erCYP2E1).…”
Section: Toxicological Consequences Of Mitochondrial Cyp2e1 Localizationmentioning
confidence: 99%
“…This induction correlates with increased oxidative stress in rats; however, the increased oxidative stress was attenuated by the addition of medium-chain triglycerides 140 . The mitochondrial-targeted antioxidant demethyleneberberine (DMB) from the Chinese herb Cortex Phellodendri chinensis also has a protective effect in acutely and chronically ethanol-treated mice 141 . DMB suppressed the 2–3-fold ethanol induction of mtCYP2E1 in liver mitochondria for both 52 kDa and 40 kDa enzyme forms (as shown by Western blot of purified mitochondrial fractions), as well as attenuated the 1.5-fold ethanol induction of overall total liver CYP2E1 (mt+erCYP2E1).…”
Section: Toxicological Consequences Of Mitochondrial Cyp2e1 Localizationmentioning
confidence: 99%
“…The literature data on the effect of alcohol on the activity of antioxidant enzymes in liver mitochondria (MnSOD, glutathione peroxidase, glutathione reductase) are controversial. For instance, the studies of Tang et al (2012) and Zhang et al (2015) showed that the activity of antioxidant enzymes decreases. In contrast, Zeng et al (2008), Larosche et al (2009), and Vidyashankar et al (2012) showed no decrease and even found an increase in the activity.…”
Section: Discussionmentioning
confidence: 99%
“…Purple sweet potato (Ipomoea batatas L., PSP) and purple potato (Solanum tuberosum L., PP) are rich in anthocyanins (Yao et al 2013) with confirmed antioxidative (Han et al 2006) and anti-inflammatory effects (Garcia et al 2014). Chronic alcohol consumption is a leading cause of broad spectrum of chronic liver diseases ranging from steatosis, steatohepatitis to cirrhosis and hepatocellular carcinoma (Zhang 2015). It is believed that chronic alcohol consumption results in the activation of innate immunity followed by the production of pro-inflammatory cytokines, such as TNF-a, and the subsequent (Kong et al 2003).…”
Section: Introductionmentioning
confidence: 99%